On conditions for the strong law of large numbers in general Banach spaces - Anna Kuczmaszewska; Dominik Szynal (International Journal of Mathematics and Mathematical Sciences)
We give Chung-Teicher type conditions for the SLLN in general Banach spaces under the assumption that the weak law of large numbers holds. An example is provided showing that these conditions can hold when some earlier known conditions fail.